2020
DOI: 10.3390/jcm9072302
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interventional Radiology for the Treatment of Hepatic Metastases from Neuroendocrine Tumor: An Updated Review

Abstract: Interventional radiology plays an important role in the management of patients with neuroendocrine tumor liver metastasis (NELM). Transarterial embolization (TAE), transarterial chemoembolization (TACE), and selective internal radiation therapy (SIRT) are intra-arterial therapies available for these patients in order to improve symptoms and overall survival. These treatment options are proposed in patients with NELM not responding to systemic therapies and without extrahepatic progression. Currently, available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 128 publications
(273 reference statements)
0
21
0
1
Order By: Relevance
“…For mCRC, studies have shown that good results can still be achieved in heavily pre-treated patients (see below) [ 38 40 ]. In NET, TARE can be considered for patients not responding to systemic therapies or have undergone prior peptide receptor radionuclide therapy (PRRT), TACE or bland embolization, which is reflected in the long median time from metastatic diagnosis to TARE (1242 days, Table 4 ) [ 35 , 41 , 42 ]. Due to the high OS generally found in NET patients, care should be taken in applying TARE in NET, as treatment-related deaths have been observed in this patient population [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…For mCRC, studies have shown that good results can still be achieved in heavily pre-treated patients (see below) [ 38 40 ]. In NET, TARE can be considered for patients not responding to systemic therapies or have undergone prior peptide receptor radionuclide therapy (PRRT), TACE or bland embolization, which is reflected in the long median time from metastatic diagnosis to TARE (1242 days, Table 4 ) [ 35 , 41 , 42 ]. Due to the high OS generally found in NET patients, care should be taken in applying TARE in NET, as treatment-related deaths have been observed in this patient population [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interventional radiology plays an important role in the therapeutic management of well-differentiated low-grade NEN, especially when liver burden is important or in the presence of a secretory syndrome [81][82][83]. Various types of liver-directed therapies are currently available, including intra-arterial therapies such as transarterial embolization (TAE), transarterial chemoembolization (TACE) and selective internal radiation therapy (SIRT), or radiofrequency ablation (RFA).…”
Section: Liver-directed Therapiesmentioning
confidence: 99%
“…TAE corresponds to catheterization of the hepatic artery and embolization using calibrated microparticles or ethiodized oil associated with gelfoam. TACE associates this procedure with the use of chemotherapeutic agents (usually doxorubicin, cisplatin, gemcitabine, or mitomycin C) based on the principle that ischemia of tumor cells increases sensitivity to chemotherapy [ 48 , 50 ]. TACE is performed either with an oily emulsion of chemotherapy (cTACE) or with drug-loaded beads (DEB-TACE).…”
Section: Endovascular Treatmentsmentioning
confidence: 99%
“…In addition to general contraindications for vascular procedures (i.e., impaired hemostasis, allergy to iodinated contrast media), specific contraindications include portal vein thrombosis and bilio-enteric anastomosis. Patients with a tumoral burden greater than 75% of the liver parenchyma or who exhibit liver function impairment (bilirubin level ≥ 3 mg/dL, ascites) should be treated carefully, as they are at high risk of acute liver failure shortly after transarterial treatment [ 49 , 50 ]. Overall, 80–86% of patients will exhibit post-procedural symptoms, mostly in the form of a post-embolization syndrome (fever, nausea, vomiting, abdominal pain, and elevated liver enzymes) that should be anticipated and treated with analgesics, steroids, and hydration.…”
Section: Endovascular Treatmentsmentioning
confidence: 99%